Infant Feeding - Breast Versus Formula 2020
DOI: 10.5772/intechopen.91865
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic and Therapeutic Role of Human Breast Milk Proteins and Bioactive Peptides against Neonatal Bacterial Infections

Abstract: Breast milk represents nature’s best mechanism to provide complete nourishment and protection to the newborn. Human breast milk acts as a store house of an array of bioactive factors, which includes antimicrobial proteins and antimicrobial peptides that confer early protection while lowering the incidence of developing various infections and exhibiting immune modulation property to activate the immune cells to fight against the invading pathogens. Among the bioactive peptides, endogenous peptides present in br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 174 publications
(180 reference statements)
0
2
0
Order By: Relevance
“…Animal models have shown that depletion of Paneth cells rich in defensins followed by enteric infection in test animals resulted in a clinical picture akin to human NEC ( 158 ). A synthetic analog of HBD (brilacidin) is tested in a phase II trial for the treatment of acute bacterial skin infections and in preclinical phase for otitis and ocular infections ( 159 ).…”
Section: Breast Milk and Mediatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Animal models have shown that depletion of Paneth cells rich in defensins followed by enteric infection in test animals resulted in a clinical picture akin to human NEC ( 158 ). A synthetic analog of HBD (brilacidin) is tested in a phase II trial for the treatment of acute bacterial skin infections and in preclinical phase for otitis and ocular infections ( 159 ).…”
Section: Breast Milk and Mediatorsmentioning
confidence: 99%
“…The ubiquitous distribution of ACE-2 in blood vessels may underlie the multi-organ pathology of COVID-19 ( 265 ). The endothelial dysfunction results in reduced vasodilation, pro-inflammatory state, and prothrombin properties ( 159 ).…”
Section: Breast Milk Factors: a New Topic Of Covid Researchmentioning
confidence: 99%